Controlled current matching in small molecule organic tandem solar cells using doped spacer layers - Schueppel, R; Timmreck, R; Allinger, N; Mueller, T; Furno, M; Uhrich, C; Leo, K; Riede, M (American Institute of Physics, 2010)
Current matching of the subcells is crucial to optimize the performance of tandem solar cells. Due to the thin film optics of organic solar cells, the position of the two subcells relative to the reflecting electrode becomes a very important issue. This is demonstrated for an indium tin oxide (ITO)/pin/pii/Al structure with thin intrinsic absorbing layers consisting of zinc-phthalocyanine and fullerene C60 and a metal-free lossless recombination contact between the subcells. By keeping the thickness of the absorbing layers constant and changing only the thickness of the inner p-doped transparent layer in 16 steps from 0 to 186 nm, the distance of the ITO-sided subcell from the reflecting electrode (Al) is systematically varied. Thus, the p-doped layer works as an optical spacer between both subcells. The influence of its thickness on the thin film optics is shown in optical simulations and confirmed with current-voltage measurements. If both subcells are separated only by the recombination contact, they are positioned in the first interference maximum of the incident light and the currents of the individual subcells nearly matches. By increasing the spacer layer thickness, the ITO-sided subcell is moved to the first interference minimum, limiting the measured short circuit current density jsc of the tandem solar cell to about 1/2 of its initial value without spacer. At a spacer thickness of about 140 nm, jsc recovers in the second interference maximum to nearly its original value. Within this series, an almost constant high fill factor of about 59% as well as a constant open circuit voltage of 1.06 V is observed, showing that the Ohmic losses in the spacer are negligible. The power conversion efficiency of these devices reaches nearly 4% in the first and approximately 3.6% in the second interference maximum, respectively, in an outdoor test at 1 sun. Furthermore, it is shown that for thicker absorber layers, an optimized current density cannot be reached in the first, but only in the second optical interference maximum, making the presented optical spacer an essential component for efficient organic tandem devices. © 2010 American Institute of Physics.